Faktor-faktor yang Mempengaruhi Minat Mahasiswa Dalam Memilih Program Studi Akuntansi di Universitas Hein Namoeto - Sahrul Posi Sahrul Ul; Heri Mariansang; Suharli Manoma (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2023)
The purpose of this study was to determine the factors that influence students' interest in choosing an accounting study program. The data used in this study were obtained from the results of distributing questionnaires which were distributed to active students in the accounting study program at Hein Namotemo University. The results of this study indicate that the career expectation factor has a positive and significant effect on student interest in choosing an accounting study program, this is evidenced by looking at the value of tcount> ttable (2.549> 1.987) with a significance of 0.015, while for the perception factor and personal characteristics it has no significant effect on students' interest in choosing an accounting study program, this is evidenced by the results of the analysis that for the perceived factor the value of tcount> ttable (1.612<1.987) with a significance of 0.115, for personal characteristics factors with a value of tcount<ttable (0.352>1.987) with a significance of 0.727. for the test results of the coefficient of determination (R Square) of 0.261 or equal to 26.1%, while the rest is influenced by other variables outside of this study.